1986
DOI: 10.1002/j.1875-9114.1986.tb03458.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Ciprofloxacin in Elderly Subjects

Abstract: The pharmacokinetics of single-dose oral ciprofloxacin 500 mg was ascertained in 12 elderly and 12 young subjects. Mean age of the elderly volunteers was 75.4 years and the mean measured creatinine clearance in this group was 40.7 ml/min. Serum and saliva were collected in serial order for 24 hours (elderly) and 10 hours (young), and assayed for ciprofloxacin by high-performance liquid chromatography. The geriatric subjects had higher serum levels throughout the sampling period, with a peak level of 3.24 +/- 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
31
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 16 publications
5
31
0
Order By: Relevance
“…As seen in previous studies (1,8), the plasma ciprofloxacin concentrations in our study were higher in elderly subjects. Increases in the C max and AUC and an increase in the half-life were observed for the elderly subjects compared with the young.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…As seen in previous studies (1,8), the plasma ciprofloxacin concentrations in our study were higher in elderly subjects. Increases in the C max and AUC and an increase in the half-life were observed for the elderly subjects compared with the young.…”
supporting
confidence: 89%
“…LeBel et al (8) reported increases in the AUC (approximately twofold), C max (43%), and elimination half-life (about twofold) for elderly subjects compared with young subjects following a 500-mg oral dose. The increases seen in these studies following oral administration were of a greater magnitude than those seen in the present study using intravenous ciprofloxacin.…”
mentioning
confidence: 98%
“…No significant differences were noted between the first dose and steady-state pharmacokinetic parameters, with the exception of an increase in the apparent volume of distribution. The results were consistent with previous studies in healthy and mildly ill elderly subjects undergoing assessment after single doses of oral ciprofloxacin in that the maximum concentration of drug in serum (Cmax) and area under the concentration-time curve (AUC) were increased compared with those of young volunteers receiving the same doses (2,3,5,9,11,15).These studies suggest that the pharmacokinetics of ciprofloxacin are altered in elderly subjects. However, comparative intravenous and oral ciprofloxacin pharmacokinetic parameters during maintenance dose therapy in the elderly have not been evaluated.…”
supporting
confidence: 90%
“…As the number of points used went from 2 to 6, the sum of squared residuals went from 5.5 to 1.8 and the coefficient of determination went from 0.993 to 0.999. (16,17,19), but the study designs, analysis, and reporting of the data have been poor to date, and the question begs further study (26).…”
Section: Methodsmentioning
confidence: 99%